Femoral neck fracture prediction by anisotropic yield criteria - Tellache, Mohamed; Pithioux, Martine; Chabrand, Patrick; Hochard, Christian (European Journal of Computational Mechanics, 2009)
The fracture risk due to osteoporosis, is undertaken with Dual-Energy X-ray Absorptiometry (DEXA) which is an average of bone mineral density measurement, without taking into account the bone structure. The objective of this study was an experimental test to solicit the human proximal femurs by a physiological configuration (one leg stance phase of walking). For this, transversely isotropic finite element models were developed from CT scan acquisition. The failure load assessment was insured by anisotropic yield behaviour criteria based on distortion energy criterion (Hill’s criterion) and taking into account the difference between tension and compression yield properties (Tsai–Wu’s criterion). The results found in this study showed the significance part of anisotropic yield behaviour of bone on proximal femur.